Analysis of Promise as a Speech Act in the Light of Satyajit Ray’s Cinema - Dipanwita Das; Pallab Sur (PRAGMATICA : Journal of Linguistics and Literature, 2025)
The current study is focusing on the analysis of promise as a speech act from a pragmatic and stylistic point of view, in correlation with Austin's speech act theory, specifically based on the instances of promises from the screenplays of Satyajit Ray’s three greatest masterpieces - his debut film, “Pather Panchali”, “Apur Sansar”, which is the third and last instalment of “Apu Trilogy:, and  "Devi". All these three films have several promise speech acts present in the film, uttered by different characters in different situations, but the role of these promises is important also from linguistic point of view as the concept of promise as a speech act as explained by Austin (1962) and, Searle (1969) also brings some conditions to the scenario which are crucial, for those promises to be considered successful. In a successful promise, there has to be an obligation creating circumstance. A successful promise depends on the promisor's ability and the promisee’s preference. We will be looking into Searle's (1969) theory, where he suggested that felicity conditions are important for a promise to be a successful speech act, i.e propositional condition, preparatory condition, sincerity, and essential condition. We will be looking out to observe the promises made and kept or left partially or completely unfulfilled by the characters, analyse them using the speech act theory, and briefly look into Ray’s spectacular cinematic world to understand the role of the promises in the climax of the films.